PENGARUH BUDAYA PATRIARKI TERHADAP PEMAHAMAN AGAMA DAN PEMBENTUKAN BUDAYA - Nina Nurmila (Karsa: Journal of Social and Islamic Culture, 2015)
Patriarchy is a system that put adult men in central and important position, while others such as women and children are positioned in relation to the interest of the patriarch (adult man). Within patriarchal system, women are positioned as wives whose job is to accompany, complement, entertain and serve the patriarch, while children are positioned as the next generation and entertainer of their father. This system affects the interpretation of religion, in this case Islam. Understanding religion by using patriarchal lenses can produce patriarchal culture which position women as always subordinate to men and that men as always superior to women, such as that men are leaders of women who manage and decide women’s affairs regardless of whether or not the men are capable or fulfilling the requirements of being leader. This religious understanding by using patriarchal lenses causes gender injustice between men and women, which contradicts Islam, as a religion which supports equality and justice and argues against patriarchy. Therefore, new religious understanding by using equal gender perspective, not patriarchal perspective, is needed.Copyright (c) 2015 by KARSA. All right reservedDOI: 10.19105/karsa.v23i1.606